Paranasal Sinuses 2017
DOI: 10.5772/intechopen.68993
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Packing after Functional Endoscopic Sinus Surgery

Abstract: This chapter was to have a systematic review and meta-analysis on the available literature in order to compare the eicacy and postoperative outcomes of nasal packing (absorbable vs. nonabsorbable) after treatment of chronic rhinosinusitis with functional endoscopic sinus surgery (FESS). The systematic review included ive studies with 241 nasal cavities in each treatment group. The prevalence of synechia in the absorbable groups ranged from 4.6 to 8.0% while nonabsorbable groups ranged from 8.0 to 35.7%. The ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Today, there are a variety of options, ranging from absorbable to nonabsorbable nasal packing, and some surgeons prefer no packing at all. Regarding postoperative pain, numerous studies have shown that nasal packing increases the intensity of pain, especially nonabsorbable nasal packing 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Today, there are a variety of options, ranging from absorbable to nonabsorbable nasal packing, and some surgeons prefer no packing at all. Regarding postoperative pain, numerous studies have shown that nasal packing increases the intensity of pain, especially nonabsorbable nasal packing 19 .…”
Section: Discussionmentioning
confidence: 99%